CPK-ECC based mutual authentication protocol for large-scale RFID system - Yao-min PAN; Zheng SHAN; Qing DAI; Feng YUE (Tongxin xuebao)
The existing RFID authentication protoco1s were short of sca1abi1ity.Taking advantage of combined pub1ic key（CPK），a CPK-ECC based authentication protoco1 was proposed considering the design demand of authentication protoco1s for 1arge-sca1e RFID system.The protoco1 imp1ements mutua1 and server1ess authentication by adoption of the e11iptic curve encryption scheme and the improved digita1 signature a1gorithm.Based on the security ana1ysis，the protoco1 can resist the existing security and privacy attacks effective1y.Compared with other ECC-based protoco1s，the server1ess protoco1 has better sca1abi1ity and performance，suitab1e for 1arge-sca1e RFID systems.